Enantioselective recognition of chiral acids by supramolecular interactions with chiral AIEgens. Issue 98 (23rd November 2021) - Xiang, Song; Lv, Panpan; Guo, Changsheng; Qi, Chunxuan; Yang, Jun-Cheng; Tian, Jingjing; Yang, De-Suo; Feng, Hai-Tao; Tang, Ben Zhong
Abstract : Chiral AIEgens enantioselectively discriminated a series of chiral acidic compounds and amino acids by supramolecular assembly. Abstract : Novel chiral AIEgens bearing optically pure amino groups were synthesized and showed excellent discrimination for a series of chiral acidic compounds and amino acids. Interestingly, after supramolecular assembly with 4-sulfocalix[4]arene, the obtained complexes showed enhanced enantioselectivity for chiral acids.